Bioactive Adrenomedullin, Organ Support Therapies, and Survival in the Critically Ill: Results from the French and European Outcome Registry in ICU Study. Issue 1 (January 2020) - Lemasle, Léa; Blet, Alice; Geven, Christopher; Cherifa, Ményssa; Deniau, Benjamin; Hollinger, Alexa; Fournier, Marie-Céline; Monnet, Xavier; Rennuit, Isabelle; Darmon, Michael; Laterre, Pierre-François; Struck, Joachim; et al.
Abstract : Objectives: Adrenomedullin has vascular properties and elevated plasma adrenomedullin levels were detected in sepsis. We assessed, in septic and nonseptic ICU patients, the relation between circulating adrenomedullin, the need for organ support and mortality, using an assay of bioactive adrenomedullin. Design: Prospective multicenter observational cohort study. Setting: Data from the French and euRopean Outcome reGistry in ICUs study. Patients: Consecutive patients admitted to intensive care with a requirement for invasive mechanical ventilation and/or vasoactive drug support for more than 24 hours following ICU admission and discharged from ICU were included. Interventions: Clinical and biological parameters were collected at baseline, including bioactive-adrenomedullin. Status of ICU survivors was assess until 1 year after discharge. The main outcome was the need for organ support, including renal replacement therapy and/or for inotrope(s) and/or vasopressor(s). Secondary endpoints were the ICU length of stay and the 28-day all-cause mortality. Measurements and Main Results: Median plasma bioactive adrenomedullin ( n = 2, 003) was 66.6 pg/mL (34.6–136.4 pg/mL) and the median Simplified Acute Physiology Score II score 49 (36–63). Renal replacement therapy was needed in 23% and inotropes(s) and/or vasopressor(s) in 77% of studied patients. ICU length of stay was 13 days (7–21 d) and mortality at 28 days was 22 %. Elevated bioactive adrenomedullin independently predicted 1) the need for organ support (odds ratio, 4.02; 95% CI, 3.08–5.25) in ICU patients whether admitted for septic or nonseptic causes and 2) the need for renal replacement therapy (odds ratio, 4.89; 3.83–6.28), and for inotrope(s) and/or vasopressor(s) (odds ratio, 3.64; 2.84–4.69), even in patients who were not on those supports at baseline. Elevated bioactive adrenomedullin was also associated with a prolonged length of stay (odds ratio, 1.85; 1.49–2.29) and, after adjustment for Simplified Acute Physiology Score II, with mortality (odds ratio, 2.31; 1.83–2.92). Conclusions: Early measurement of bioactive adrenomedullin is a strong predictor of the need of organ support and of short-term mortality in critically ill patients. Abstract : Supplemental Digital Content is available in the text.